Experiential avoidance predicts persistence of major depressive disorder and generalized anxiety disorder in late adolescence - Mellick, William H. (J Clin Psychiatry, 2019)
OBJECTIVE: Experiential avoidance (EA) is a transdiagnostic construct that may underlie the high comorbidity between major depressive disorder (MDD) and generalized anxiety disorder (GAD). This analysis used data from a longitudinal study (conducted September 2010 – April 2016) to examine whether adolescent EA varies by MDD/GAD symptomology trajectory and predicts said trajectories. Longitudinal associations between EA, anxiety, and depression symptoms were also examined. METHODS: Fifteen to 20 year-old adolescents (N =183) were followed for two years with a comprehensive assessment battery. Symptom trajectory modeling, using weekly symptom ratings, identified 4 MDD and 4 GAD trajectories which were collapsed to form combined MDD/GAD trajectory groups: Persistent (n = 81), High-Decreasing (n = 44), Normal-Increasing (n = 37), and Minimal (n = 21). Analyses of covariance, structural equation modeling, and linear regression analyses were performed. RESULTS: Persistent adolescents had higher EA versus other groups (p-values ≤ 0.001), with greater EA stability versus High-Decreasing adolescents (p = 0.008). EA predicted anxiety and depressive symptoms alike (p-values ≤ 0.005), which in turn did not predict EA (p-values ≥ 0.188). EA, at both time points, predicted combined MDD/GAD trajectories after adjusting for depressive and anxiety symptoms and other confounders (p-values < 0.001). CONCLUSION: EA appears to be an important predictor of MDD/GAD symptomology in older adolescents, potentially serving as a treatment target. Findings suggest a possible trait-like nature for EA, perhaps increasing risk for the emergence and persistence of MDD and/or GAD. TRIAL REGISTRATION: ClinicalTrials.gov identifier: .